Overview of COVID-19 Pandemic: Its Management and Prevention in Light of the Indian Traditional Medicine System - Singh, Lav; Singh, Arpit; yadav, Divyanshu; Chhavi, Apurv; Srivastava, Ravi P.; Pandey, Shivaraman; Dixit, Pooja; Ramakant; Verma, Praveen Chandra; Saxena, Gauri (Current Traditional Medicine, 2023)
With the global death toll nearing 3.3 million, India being amongst the top 4 countries, the condition is more than fearsome. World Health Organization (WHO) recommends one doctor per 1000 population ratio, but India lags it by one doctor to 1456 people, which sets a lot of pressure on the healthcare system. Traditional remedies are becoming increasingly popular in India as a result of the lack of a proper medical system. Due to the rich diversity of medicinal herbs and drugs, India has been managing health issues with its 5000 years old medication system. Amidst all this, the traditional medicine system has given relief to plenty of diseases and remains the primary defence system against COVID-19. Therefore, COVID-19 is also managed by its different medicinal systems, which are collectively known as the AYUSH regime. It had been a recognized system to tackle diseases in the past. In this mini-review, we performed a deep study of the Indian traditional medicine system in managing the COVID-19 situation.
Keywords: medicinal plant